Programa educativo de bioseguridad para el buen uso de plaguicidas en el barrio El Pucará en relación con la calidad de vida de los agricultores de la zona en el año 2014. - Calvachi Moreno, Juan Carlos (2015)
Background: The community of Barrio El Pucará is highly exposed to pesticides, ignorance of the rules of handling and proper disposal of waste, lack of control of health authorities in the sale of pesticides, lack of side effects, results in socio-economic and legal problems, poor quality of life with direct influence on morbidity and mortality. Objective: To identify the level of awareness among the community about the proper handling of pesticides their health damage and propose a Biosafety Education Program, to reduce exposure to pesticides and improving the quality of life. Methods: A survey was applied to 30 farmers in the study area to evaluate their knowledge of the use and management of pesticides as well as on adverse exposure to pesticides and prevention effects. Results: Participants know the rules of proper management of pesticides and biosecurity measures. Conclusions: The lack of biosafety regulations and proper handling of pesticides affects the quality of life of the population. Education Program Biosafety is feasible, easy to assimilate, allow adequate education about handling rules, which this group will improve the quality of life and therefore the morbidity and mortality. Descriptors: ignorance, no control, lack of interest.